Zimbabwe’s Youth Empowerment Programme and Poverty Alleviation amongst Youths in Gweru Urban District (Journal of Governance and Development (JGD), 2020)
Zimbabwe’s youth empowerment programme was a public-private partnership between the Government of Zimbabwe and some Zimbabwean financial institutions. The aim of the programme was to alleviate poverty amongst youths through the provision of micro credit. Established in 2009 as the panacea for Zimbabwe’s youth empowerment challenges, there is very little credible data on the performance and effectiveness of this noble intervention that was criticised by some as partisan. Therefore, the purpose of this paper is to evaluate the extent to which Zimbabwe’s youth empowerment programme was able to achieve its main objective of alleviating poverty amongst the youths in Zimbabwe’s Gweru Urban District. The paper adopts a qualitative case study research design utilising both primary and secondary sources of data. Primary data was collected through semi- structured interviews with key informants as well as researcher observation. Secondary data was mainly obtained through searches of both physical and online libraries and repositories. Qualitative content analysis is the method used to analyse the data. The research findings reveal that the objectives of the programme were indeed relevant to the current challenges being faced by the youth in Zimbabwe. However, the programme had very little effect on youth poverty and unemployment in Gweru Urban District which remains high. Possible reasons for the limited effectiveness could be the fact that few youth projects were funded as compared to the number of youths that were in need of funding. The high rate of collapse of the youth projects funded coupled with the failure to sustain production levels achieved after accessing the loans also meant that chances of employment creation were limited. There were however, a few success stories noted by the study. The study recommends more training for beneficiaries if such programmes are to be more effective in future. This study is of significance as it adds to the existing body of knowledge the effectiveness of micro credit as a poverty alleviation strategy. Moreover, the paper is of importance to the Zimbabwe government and other development agents as it provides credible and perhaps more reliable accounts on the performance and effectiveness of Zimbabwe’s youth empowerment programme.